Write and Let Go: An Online Writing Program for University Students - Batista, João; Marinai, Janine C.; Gouveia, Melissa; Oliveira, João Tiago; Gonçalves, Miguel M. (Frontiers in Psychology, 2022)
Background There are a plethora of studies on expressive writing and positive writing interventions, but few have addressed the combination of both paradigms. Additionally, research on the role of ambivalence toward change in the context of writing-based interventions is lacking. Ambivalence toward change is a natural movement of approaching and avoiding change that may occur in various situations. In psychotherapy, its resolution is associated with successful outcomes. Aim This study tested the efficacy of a combination of expressive and positive writing paradigms in an internet-based intervention to improve university students’ mental health. Additionally, focusing participants on a current, unresolved problem allowed us to explore the possible role of ambivalence toward change as a mediator of the intervention’s results. Methods We recruited 172 participants who were randomly divided into experimental (n = 85) and control (n = 87) groups. The intervention consisted of the identification of a current problem and four writing tasks on consecutive days. Assessment was conducted at baseline and posttest in both groups and at follow-up in the experimental group. Participants in the experimental condition were also assessed after each task. Measures of anxiety, depression, rumination, ambivalence toward change, distress, and wellbeing (optimism, affect, and satisfaction with life) were collected. Results Multivariate analysis of variance (MANOVA) showed that participants in the experimental group had a significant decrease from baseline to posttest in ambivalence toward change and rumination when compared with the control group. These results were maintained at follow-up. No differences were found in the remaining measures. Within the experimental group, ambivalence toward change, rumination, and distress significantly decreased throughout the intervention and the exploratory mediation analysis indicated that ambivalence toward change partially mediated the improvements in rumination and distress. Discussion Considering different perspectives about a current problem and using a combination of expressive and positive writing fostered the reduction of ambivalence toward change and rumination. Ambivalence toward change reduction after the second writing task may have created optimal conditions for the subsequent decrease in rumination and distress. Future studies should replicate this finding and dismantle the components that are more adequate in changing these variables.